Nonaqueous sol‐gel synthesis of InTaO4 nanoparticles and their assembly into macroscopic aerogels. Issue 10 (21st June 2017) - Rechberger, Felix; Tervoort, Elena; Niederberger, Markus
Abstract: Due to their band gap energy, metal tantalates absorb both ultraviolet and visible parts of the solar spectrum, which is beneficial to applications in photocatalysis. However, tantalates are very challenging to synthesize. In comparison to traditional solid‐state reactions, which often lead to impurities, wet‐chemical approaches starting from molecular precursors offer better homogeneity. In this study, amorphous InTaO4 nanoparticles were synthesised in a nonaqueous sol‐gel method. Subsequent annealing at 800°C yielded crystalline and phase‐pure nanoparticles. In addition, the amorphous nanoparticles could be used as building blocks for the assembly into macroscopic gels by careful centrifugation. After supercritical drying, the three‐dimensionally interconnected microstructure was preserved, resulting in highly porous aerogel monoliths with a large surface area of 357 m 2 g −1 . Upon calcination, crystallization and 46% shrinkage of the aerogel occurred and a decrease in surface area to 49 m 2 g −1 was observed. Uniaxial compression tests revealed the mechanical stability of these nanoparticle‐based aerogels. Although the large surface area and the ability to absorb visible light, combined with the unique mechanical properties, are ideal prerequisites to make these aerogels promising for photocatalytic reactions, the degradation of methylene blue only showed limited success.